Concentration of Heavy Metals in Soils under Cemetery Occupation in Amazonas, Brazil - Prestes da Silva, Rafael Bel; Costa Campos, Milton Cesar; Silva, Laercio Santos [UNESP]; Brito Filho, Elilson Gomes de; Leite de Lima, Alan Ferreira; Pinheiro, Elyenayra Nogueira; Cunha, Jose Mauricio (Taylor & Francis Inc, 2019)
The study aimed to quantify Cd, Cr, Cu, Ni, Pb, Zn, Al, Fe, and Mn concentrations in soils due to cemetery occupation in the Brazilian Amazon in order to assess the potential of environmental contamination. Atotal of 45 samples were collected in the 0.00-0.40, 0.40-0.80, and 0.80-1.20m layers, with trenches opened in a Gleysol (Cemetery - I) and Cambisol (Cemetery - II) to determine Fe, Al, Mn, Cr, Cu, Cd, Ni, Pb, and Zn contents. Chemical and particle size analyses were also performed. Soil sample digestion was based on the EPA 3051A method and metal concentrations were determined by ICP-OES. The results were submitted to descriptive statistics, control charts, and multivariate statistics by principal components. The effective increase in Fe, Cr, Cu, Ni, Pb, and Zn concentrations indicates ahigher potential of contamination by these metals due to cemetery activity, with concentrations above the recommended reference values for Brazilian Amazon sediment soils. Soil shows ability to return, resilience, to the chemical quality and natural concentrations of potentially toxic elements with the inactivation of cemetery activities. The clay fraction and organic matter are the main coordinators of metal dynamics in soil profiles.
Keywords: Urban expansion; cemeteries; soil contamination; control chart